Designing A Cooking Procedure Simulation Game During the Pandemic In The Food and Beverage Industry Using The Design Play Experience Method - Azhari, Anissa; Yuniarti, Rezki; Komarudin, Agus (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Covid-19 has become one of the world's problems after its first appearance at the end of 2019. At its peak, the COVID-19 pandemic affected many industrial sectors, including the food and beverage industry and, in this case, Indonesia. The main focus in running the industry is health protocols for handling both the cooking and serving processes, which must pay more attention to cleanliness and health to reduce the spread of the COVID-19 virus. Standard operating procedures can be simulated in the game as a lesson in cooking procedures for professionals and the general public. Learning and experience in playing games is a challenge in developing simulation games, so the DPE (Design, Play, and Experience) framework is the choice for the game design method in this research. The study results were evaluated by 15 respondents who tried this game with a distribution of 6 workers in the food and beverage industry and 9 people who were not workers in the food and beverage industry. Game development with the DPE framework gets results in the learning aspect of the experience component for simulation with an average value of 88.70%. For the experience learning aspect, the knowledge players gain after playing the game is 84.87%, with very appropriate criteria.